Estimation of citywide air pollution in Beijing. - Jin-Feng Wang (Public Library of Science (PLoS), 2013)
There has been discrepancies between the daily air quality reports of the Beijing municipal government, observations recorded at the U.S. Embassy in Beijing, and Beijing residents' perceptions of air quality. This study estimates Beijing's daily area PM(2.5) mass concentration by means of a novel technique SPA (Single Point Areal Estimation) that uses data from the single PM(2.5) observation station of the U.S Embassy and the 18 PM(10) observation stations of the Beijing Municipal Environmental Protection Bureau. The proposed technique accounts for empirical relationships between different types of observations, and generates best linear unbiased pollution estimates (in a statistical sense). The technique extends the daily PM(2.5) mass concentrations obtained at a single station (U.S. Embassy) to a citywide scale using physical relations between pollutant concentrations at the embassy PM(2.5) monitoring station and at the 18 official PM(10) stations that are evenly distributed across the city. Insight about the technique's spatial estimation accuracy (uncertainty) is gained by means of theoretical considerations and numerical validations involving real data. The technique was used to study citywide PM(2.5) pollution during the 423-day period of interest (May 10, 2010 to December 6, 2011). Finally, a freely downloadable software library is provided that performs all relevant calculations of pollution estimation.